Supersymmetric index for half BPS black holes in N=2 supergravity with higher curvature corrections - Subramanya Hegde; Ashoke Sen; P. Shanmugapriya; Amitabh Virmani (Journal of High Energy Physics)
Abstract We compute the supersymmetric index of half BPS black holes in N=2 supergravity with higher curvature corrections and show that the result agrees with the degeneracy of supersymmetric extremal black holes carrying the same charges. Both sides of the computation are done gravitationally.